Find Tuition/Enrichment Centres

AskQ logo

STUCK ON HOMEWORK?

ASK FOR HELP FROM OUR KIASUPARENTS.COM COMMUNITY!

Question

Answer

  Hafiz Mariah
At first 4u 1u
Change – $60 + $18
In the end 1p 3p

1p = 4u – 60

3p = 1u + 18

3(4u – 60) = 1u + 18

12u – 180 = 1u + 18

11u = 198

1u = 18

At first, Mariah had 1u = $18

0 Replies 0 Likes ✔Accepted Answer

Hope this answer your question.

Owlinker
owlinker.com
FB Owlinker

0 Replies 0 Likes

At first, 

H : M = 4 : 1 = 4u : u

After the changes,

(4u-60) : (u +18) = 1 : 3

=>

u +18 = 3 x (4u – 60) 

u + 18 = 12u – 180

12u – u = 180 + 18

          u = 18

M = u = 18

 

1 Reply 0 Likes

Hi

Can u explain why need the 3x is on Hafiz instead of Mariah? 

Question stated Mariah had 3 times as much as Hafiz. 

u +18 = 3 x (4u – 60)  – i dun understand this part. 

1 Reply 0 Likes

Hi,

Mariah had 3 times as much as Hafiz; therefore,

M           =   3                               H

as

M= u + 18

H=4u-60

(u+18) = 3 (4u-60)

 

0 Replies 0 Likes
Find Tuition/Enrichment Centres